The synthesis of near-infrared reflective blue ceramic pigment of Co1-x Mgx AI2O4 - Rakkwamsuk, Pattana; Supothina, Sitthisuntorn; Pansukhumthana, Lada; Tangkittimasak, Teerasak (Bulletin of Applied Sciences, 2022)
This paper presents the research and development of blue ceramic pigment synthesized by solid-state reaction of cobalt aluminate doped with magnesium oxide that formed complex inorganic compound pigment (CICP) of Co1-x Mgx AI2O4 The pigment offered shades of blue and high reflectivity in the near-infrared (NIR) region. The pigment can be used as a vehicle for a high solar reflective coating that reduces heat stored in building structures, promotes energy conservation in an air-conditioning system, and enhance human thermal comfort in the building. The synthesis was performed by ball-milling raw materials composed of COO, MgO and AI2 03, at various compositions to reactively form Co1-x Mgx AI2O4 in the calcination process at 1,200, 1,300 and 1,400 °C, where x was varied between 0 and 1. The calcined compound was then washed, oven-dried and ground, that yielded powdered pigment with the shade of blue. The color of pigment, measured and computed in compliance with CIEL*a* b*, did not alter as the calcining temperature changed but varied significantly with x. As x increased, the color changed from deep blue to light blue and became white as x was equal to 1.0. The blue pigment possessed high solar reflectance in the NIR region. Its reflectance increased with x. It was found that the pigment synthesized with x = 0.8, Co0.2 Mg0.8 AI2O4, and calcined at 1,300 °C offered the highest NIR reflectance at 66.8%